2021
DOI: 10.3390/ma14081823
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Nanobubbles on the Mechanical Strength and Watertightness of Cement Mixtures

Abstract: This study analyzed the effects of applying highly concentrated hydrogen nanobubble water (HNBW) on the workability, durability, watertightness, and microstructure of cement mixtures. The number of hydrogen nanobubbles was concentrated twofold to a more stable state using osmosis. The compressive strength of the cement mortar for each curing day was improved by about 3.7–15.79%, compared to the specimen that used general water, when two concentrations of HNBW were used as the mixing water. The results of mercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…With the decrease in the micro-nano bubble diameter, the negative zeta potential as well as surface tension increase. This contributes to maintaining high stability of the micro-nano bubble in the liquid [34]. Water is pulled by the surface tension into the capillary that is created between the particles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…With the decrease in the micro-nano bubble diameter, the negative zeta potential as well as surface tension increase. This contributes to maintaining high stability of the micro-nano bubble in the liquid [34]. Water is pulled by the surface tension into the capillary that is created between the particles.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high negative potential, water is further dispersed in the cement mixture microstructure. This contributes to the formation of a homogeneous and tight mixture [34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kim et al experimentally confirmed the pore size distribution and porosity in the hydrate due to the high concentration of HNB through mercury intrusion porosimetry (MIP). In this study, as the CH (about 1 µm) was gradually consumed and became an irregular shape, C-S-H (<0.1 µm) gradually developed, resulting in a smaller internal pore size and improved watertightness and durability [ 51 ]. The hydration degree (α) of the cement paste cured in water for seven days, as determined via Bhatty’s method, was 46.56% for Case A, 57.97 % for Case B, and 67.17 % for Case C. Compared to Case A, the hydration degrees for Cases B and C showed improvements of 11.41% and 20.61%, respectively.…”
Section: Resultsmentioning
confidence: 99%